Novas estruturas fotônicas: I – Auto-organização de estruturas 1D de Te; II – Biopolímeros e plásticos reutilizados multifuncionais - Silva, Robson Rosa da [UNESP] (2016)
One-dimensional Te nanostructures (Te1D) in the shape of whiskers, wires and helices were prepared by a facile one-pot synthesis in the presence of aqueous Pluronic® F68 solution at low temperatures (< 100 ºC) and ambient pressure. The shape of Te1D nanostructures could be manuvered according with the reaction kinectics. We evaluate some techniques to assemble Te1D nanostructures on the pursuit for complex nanoarchitectures. Bundles of Te nanowhiskers and nanowires were achieved by self-assembly in liquid-liquid interface or by drop-cast technique in Si/SiO2 substrates. 1D hybrid structures have been conceived by using Te1D nanostructures as sacrificial template to attach metallic nanoparticles or even produce metallic 1D nanostructures. For example, 1D hybrid nanostructures were easily prepared by decorating Te nanowires with Ag nanoparticles in aqueous solution of poly(vinylpyrrolidone). Au 1D nanostructures with nodular-like shape were prepared by galvanic displacement of Au3+ ions in a mixture of Te nanohelices, ascorbic acid and an aqueous solution of poly(vinylpyrrolidone). Furthermore, Te1D nanohelices were functionalized with a layer of resorcinol-formaldehyde resin at mild synthesis conditions. The RF resin allowed us to fashion an intermediate pathway to explore the deposition of optically active compounds like Tb3+ hydroxylcarbonate or Au nanoparticles. Seeking practical applications, these nanostructures should be hosted over rigid or flexible films possessing excellent optical properties. Pure natural polymers and epoxy sol-gel hybrids films were evaluated as potential host for luminophors. The fabrication of epoxy hybrids is based on the incorporation of 3-glycidoxypropyltrimethoxysiloxane on the homogenous solution of natural polymer with subsequent casting over flat surface. Particularly, flexible silk fibroin and cellulose acetate films and their derivative hybrids displayed excellent optical properties to host optically active compounds. For instance, red emitting Eu3+ compounds and fluorescent dyes were hosted on pure natural polymer and hybrid films and the optical features of the luminescent films were investigated thoroughly. Distributed feedback dye-lasers were fabricated by doping silk fibroin diffraction gratings with Rhodamine 6G. Owing its ability to mimic patterned surfaces at nanoscale resolution, dye-doped SF gratings were fabricated using replica-casting patterning against a commercial blank digital versatile disc as template. A modified DFB Laser based on SF films with Ag or SiO2 light scattering particles randomly distributed on the grating unveiled an enhancement of laser intensity withal narrowing of emission peak linewidth. Flexible and highly transparent SF- and CA-epoxy hybrids (> 85%) containing red fluorescent Eu3+ b-diketonate complex and YVO4:Eu3+ nanoparticles at low relative content (< 5 wt%) were tailored. In general, the outcome is homogeneous films with epoxy and/or unhydrolized alkoxysilane functions available for further chemical modification. Owing the limited feedstock of natural polymers for high demanding production of optical devices, it is equally important develop materials based on the reuse of synthetic polymers. Thin films of polystyrene were conceived by dissolving waste-recovered expanded-polystyrene (EPS) in D-limonene, a green solvent from citrus oil. Transparent EPS films doped with Eu3+ b-diketonate complex displayed excellent transparency and light waveguiding, These assertions provide a framework that motivates the research on a) engineering of 1D hybrids nanostructures with tunable optical properties and b) flexible natural polymer/epoxy hybrid with enhanced functionality or plastic recycled as potential optical hosts sought in photonic applications.